On the issue of uniformity of judicial practice in resolving corporate disputes on invalidation of transactions in Kazakhstan - Baikenzhina, Sh.T. (Академик Е.А. Бөкетов атындағы Қарағанды университетінің баспасы, 2025)
The article is devoted to the analysis of issues of compliance with the uniformity of judicial practice in Kazakhstan in the resolution of corporate disputes related to the recognition of transactions as invalid. The study examines the legal grounds for invalidating corporate transactions. As a result of the invalidity of the corporate transaction, the key problems arising in the judicial practice of the Republic of Kazakhstan have been identified. When analyzing some cases in civil cases, the approaches of courts to resolving such disputes are analyzed, including civil cases on corporate disputes that were canceled by the cassation instance. A special focus is on the need to ensure legal certainty and predictability of court decisions in order to form a uniform practice and a stable corporate environment. Based on the results of the analysis of judicial practice, recommendations are proposed to improve law enforcement practice to achieve greater uniformity in resolving corporate disputes, which can help increase the confidence of the business community in the judicial system and strengthen the rule of law in the economic sphere. This research was conducted as part of the preparation of a dissertation for the degree of Doctor of Philosophy (PhD) and will form the basis for writing a chapter on compliance by courts of the Republic of Kazakhstan with uniform judicial practice in resolving corporate disputes.
Keywords: corporate dispute; uniformity of judicial practice; court; revision of judicial acts; judicial decision